Biodiesel production from grease trap waste and its purification using activated biochar derived from woodchips biomass - Jariah, Nurhanani Fatihah (2021)
Depletion of non-renewable fossil fuels and growing environmental awareness have attracted extensive research worldwide towards biodiesel. It is clean, safe, biodegradable, and renewable. Presently, grease trap waste (GTW) appears to be an alternative feedstock for biodiesel production, while woodchips biomass is more suitable as bioadsorbent for biodiesel purification. In this study, production of biodiesel from grease trap waste was achieved by using both esterification and transesterification processes. After esterification, the free fatty acid (FFA) content in the esterified oil is reduced to 0.61% with 95% of FFA conversion. Under the best conditions of 6:1 methanol to oil molar ratio, 1.5 wt% catalyst loading, at 40°C for 2 h, 87% of fatty acid methyl ester (FAME) yield was achieved. The purification of crude biodiesel using activated biochar from woodchips biomass was performed using different adsorbent loadings (0.025 to 0.125 g/L) under continuous stirring condition at 150 rpm for different residence time (20 to 100 mins). The activated biochar was characterised by Brunauer-Emmett-Teller (BET) surface area, scanning electron microscopy with energy dispersive X-ray (SEM-EDX), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Approximately, 98.2% of free fatty acid and 67.9% of soap content were successfully removed after purification at 0.05 g/L of activated biochar loading for 1 h. The fuel properties of the purified biodiesel (density, kinematic viscosity, flash point, cloud point, and pour point) were found to be in good agreement with the EN14214 and ASTM D6751 standards outlined for FAME fuel engines. Therefore, this study has shown the potential and the effectiveness of using waste material both as feedstock and purifier in biodiesel production; making the process more sustainable for the environment.